Racial Bias, Social–Emotional Competence, and Teachers' Evaluation of Student Behavior. Issue 1 (15th December 2021) - Ura, Sarah K; d'Abreu, Ana
Abstract: Children of color are disproportionately referred for discipline in schools and subsequently receive harsher punishments than their peers. Teachers' implicit bias has been identified as a possible source of these disparities, particularly for Black boys. However, teachers' social–emotional competence (SEC) may mitigate biased responses to Black students' behavior and make them likely to interpret concerning or disruptive behavior as a need for counseling rather than discipline referral. This study examined the effect of teachers' SEC (rated high, medium, or low) on the likelihood of referring a student for counseling, given a student's race, with a sample of 164 teachers. Results showed that teachers may have racial bias regardless of their level of SEC, although it manifests differently depending on the type of student behavior. The article concludes with the discussion of the importance of a culturally responsive, trauma-informed approach to evaluation of student behavior, and implications for school social workers' practice.